The Effectiveness Of Using Ice Cream Stick Media In Increasing The Calculation Of Children Aged 5-6 Years Old In Nagari Muara Sakai Pesisir Selatan District - Dona Afriza; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is motivated by the low numeracy skills of children. It is suspected that the child's low numeracy ability can be caused by many factors, including inappropriate learning methods, lack of parental/environmental support, unattractive learning facilities/media, and low levels of children's intelligence. This study aims to determine the ability to increase the effectiveness of using ice cream sticks in improving the numeracy skills of children aged 5-6 years in Nagari Muaro Sakai, Pesisir Selatan Regency. The type of research is quantitative with a quasi-experimental method with a pretest and posttest design. The population of this study were 20 children aged 5-6 years in Nagari Muaro Sakai, with a study sample of 8 children taken by purposive sampling technique. Data analysis used paired sample t-test. Before being given the action (pretest) the child's numeracy ability was categorized as not yet developed, after being given the action (posttest) the child's numeracy ability was categorized as developing and there was an influence of ice cream stick media on the child's ability to count. Sig 0.000 < 0.05. It is suggested to AUD parents and educators to use ice cream stick media in developing numeracy skills in children.Keywords: Ice cream stick media, Counting Ability